The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/yea.3236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization the carotenoid productions and profiles of three Rhodosporidiumtoruloides mutants from Agrobacterium tumefaciens‐mediated transformation

Abstract: The red yeast Rhodosporidium toruloides is a known lipid producer capable of accumulating large amounts of triacylglycerols and carotenoids. However, it remains challenging to study its carotenoid production profiles owing to limited biochemical information and inefficient genetic tools. Here we used an Agrobacterium tumefaciens-mediated transformation (ATMT) to change its carotenoid production and profiles. We constructed R. toruloides NP11 mutant libraries with ATMT, selected three mutants with different col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This was because colonies obtained by the Agrobacterium -mediated transformation usually had the expression cassette randomly integrated into the genome, and thus could have varied phenotypic profiles. 17 Indeed, many R. toruloides transformants were tested to find good fatty alcohol producer in a recent study. 7 Our preliminary results showed that 4 out of 24 transformants, namely, NP-Pta-4, NP-Pta-6, NP-Pta-15 and NP-Pta-20, grew much faster than the wild strain NP11.…”
Section: Resultsmentioning
confidence: 99%
“…This was because colonies obtained by the Agrobacterium -mediated transformation usually had the expression cassette randomly integrated into the genome, and thus could have varied phenotypic profiles. 17 Indeed, many R. toruloides transformants were tested to find good fatty alcohol producer in a recent study. 7 Our preliminary results showed that 4 out of 24 transformants, namely, NP-Pta-4, NP-Pta-6, NP-Pta-15 and NP-Pta-20, grew much faster than the wild strain NP11.…”
Section: Resultsmentioning
confidence: 99%
“…Little genetic analysis of the endogenous enzymes for carotenoid biosynthesis in R. toruloides has been carried out to date. A number of mutants with improved carotenoid yields have been generated but the exact genetic changes responsible have not been reported (Bao et al, ; C. Zhang et al, ) The earlier mentioned T‐DNA mutagenesis study reported decreased carotenoid production upon integration into the intron of R. toruloides hypothetical gene RTHO_00032 or the exon of hypothetical gene RTHO_07952 , which is predicted to encode a bZIP transcription factor (Lin et al, ). The same study also reported that T‐DNA insertion into the promoter of hypothetical gene RTHO_07650 (encoding a putative DUF1479 domain protein) increased carotenoid yields, exemplifying that regulation plays an important role in carotenoid biosynthesis, an assertion that would benefit greatly from integrative analysis of expression data with a comprehensive model of metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…T‐DNA insertion positions were identified using TAIL‐PCR according to the previous study [12]. Specific primers (RB‐0‐a, RB‐1‐a, and RB‐2a) and arbitrary primers (LAD1, LAD2, LAD3, and LAD4) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The AC1 primer was cooperated with RB‐1‐a and RB‐2‐a and used in the primary TAIL‐PCR and the secondary TAIL‐PCR. The conditions for PCR were referenced in the previous study [12], and the products were analyzed by 1.0% (w/v) agarose gels. SanPrep Column DNA Gel Extraction Kit of Sangon Biotech was used to purify the most specific product with the highest intensity.…”
Section: Methodsmentioning
confidence: 99%